2006
DOI: 10.2460/javma.229.4.542
|View full text |Cite
|
Sign up to set email alerts
|

Sodium iodide I 131 treatment of dogs with nonresectable thyroid tumors: 39 cases (1990–2003)

Abstract: Results suggested that 131I therapy may result in prolonged survival times in dogs with nonresectable thyroid tumors, regardless of serum thyroxine concentration prior to treatment. Dogs undergoing 131I therapy should be monitored for signs of bone marrow suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 23 publications
2
86
1
4
Order By: Relevance
“…A palpable goiter may develop in dogs treated chronically with potentiated sulfonamides (Seelig et al, 2008;Taeymans and O'Marra, 2009). Use of high dose radioactive iodine (iodine-131 [ 131 I]) for treatment of thyroid neoplasia also results in hypothyroidism (Turrel et al, 2006). In a report of 15 dogs undergoing bilateral thyroidectomy for treatment of thyroid tumors, approximately 50% of dogs required long-term thyroid hormone supplementation (Tuohy et al, 2012).…”
Section: Miscellaneous Causesmentioning
confidence: 99%
“…A palpable goiter may develop in dogs treated chronically with potentiated sulfonamides (Seelig et al, 2008;Taeymans and O'Marra, 2009). Use of high dose radioactive iodine (iodine-131 [ 131 I]) for treatment of thyroid neoplasia also results in hypothyroidism (Turrel et al, 2006). In a report of 15 dogs undergoing bilateral thyroidectomy for treatment of thyroid tumors, approximately 50% of dogs required long-term thyroid hormone supplementation (Tuohy et al, 2012).…”
Section: Miscellaneous Causesmentioning
confidence: 99%
“…Surgical resection alone demonstrated a median survival of 20.5 months in a study of 20 dogs without evidence of metastasis [13]. A study of 39 dogs with nonresectable thyroid tumors treated with iodine 131 demonstrated a median survival time of 28 months (tumor restricted to within the neck) and 12 months for dogs with distant metastasis [14]. A similar case study in 65 dogs evaluated the effectiveness of 131 I as an adjuvant to therapy with a median survival of 34 months compared to 30 months using 131 I as a single agent [15].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, pulmonary metastasis is identified in 30% to 40% of dogs, which contrasts with histopathologic studies that report metastasis in up to 80% of dogs at time of death (Leav et al, 1976;Brodey and Kelly, 1968;Sullivan et al, 1987;Marks et al, 1994;Carver et al, 1995;Turrel et al, 2006). In clinical studies, pulmonary metastasis is identified in 30% to 40% of dogs, which contrasts with histopathologic studies that report metastasis in up to 80% of dogs at time of death (Leav et al, 1976;Brodey and Kelly, 1968;Sullivan et al, 1987;Marks et al, 1994;Carver et al, 1995;Turrel et al, 2006).…”
Section: Radiographymentioning
confidence: 89%